If the shoe fits - Murphy, Julie, 1985- (Meant to be, 2021)
"In this modern-retelling of Cinderella, plus-size Cindy dreams of becoming a shoe designer. But when a spot opens up on her stepmother's famous reality dating TV competition, Cindy is thrust into the spotlight in ways she never thought possible"--